2011
DOI: 10.1002/bit.23054
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a cutinase membrane reactor for the production of biodiesel in organic media

Abstract: The enzymatic transesterification of oils with an alcohol, using recombinant cutinase of Fusarium solani pisi microencapsulated in sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/isooctane reversed micelles, was performed in a membrane bioreactor (MBR). A tubular ceramic membrane with a nominal molecular weight cut off of 15,000 Da was used to retain the enzyme, and characterized in terms of rejection coefficients of the reaction components by transmission experiments. The performance of the MBR in a total recir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Biodiesel conversion reached 99% in 15 h, and the removal of glycerol maintained the reaction rate over the entire experimental run. On the other hand, Badenes et al [176] reported the production of biodiesel in MBR using a tubular hydrophobic ceramic membrane to retain a recombinant cutinase (an enzyme with lipolytic activity) microencapsulated in sodium bis(2-ethylhexyl) sulfosuccinate/isooctane reversed micelles. It is important to note that although a relatively high productivity (198 g product / day/g enzyme ) has been reported, the conversion was very low (42%).…”
Section: Other Reactor Configurationsmentioning
confidence: 98%
“…Biodiesel conversion reached 99% in 15 h, and the removal of glycerol maintained the reaction rate over the entire experimental run. On the other hand, Badenes et al [176] reported the production of biodiesel in MBR using a tubular hydrophobic ceramic membrane to retain a recombinant cutinase (an enzyme with lipolytic activity) microencapsulated in sodium bis(2-ethylhexyl) sulfosuccinate/isooctane reversed micelles. It is important to note that although a relatively high productivity (198 g product / day/g enzyme ) has been reported, the conversion was very low (42%).…”
Section: Other Reactor Configurationsmentioning
confidence: 98%
“…Owing to the segregation of two immiscible liquids by the membrane, MBR is commonly employed for biphasic systems. Badenes et al (2011) reported on the production of biodiesel in MBR using recombinant cutinase microencapsulated in sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/isooctane reversed micelles. A tubular ceramic membrane with a nominal molecular weight cutoff of 15 kDa was used to retain the enzyme.…”
Section: Bioreactor Designmentioning
confidence: 99%
“…However, CEH have also been used in the food and flavor industry, in the biocatalytic resolution of pharmaceuticals, synthesis of ester and amino acid derivatives, the production of fine chemicals, and agrochemicals; they have also been used in biosensors, in bioremediation, and in the cosmetics and fragrances sector [3][4][5][6]. Furthermore, in the last few years, several works that illustrate the importance of transesterification reactions catalyzed by lipases and cutinases for biodiesel production have been published [7][8][9]. The demand for highly active preparations of CEH enzymes has led to focus research on the producer microorganisms, including culture strategies.…”
Section: Introductionmentioning
confidence: 99%